2022
DOI: 10.1002/hpm.3569
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening the ICUs' human resource‐related responses to Covid‐19: A rapid review of the experience during the first year of public health emergency

Abstract: By drawing on macro‐categories of key human resource (HR) management interventions recommended by the Organization for Economic Co‐operation and Development (OECD) during the Covid‐19 pandemic, this study aimed to explore whether and how Intensive Care Units (ICU) have strengthened their HRs during the first year of Covid‐19 emergency. A rapid review was conducted to provide a quick synthesis of the literature in English identified in the Web of Science Core Collection (WoS), PubMed, and Scopus databases. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Data were collected up to May 2021 for the exposed and in 2019 or 2021 for the comparison group: as a consequence, the available findings reflect substantially the first year of the pandemic, when some strategies to increase the service capacity were implemented. Therefore, long-term consequences of these changes have not been evaluated [ 37 ]. Some studies may have been performed later and/or submitted to a journal for peer review.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected up to May 2021 for the exposed and in 2019 or 2021 for the comparison group: as a consequence, the available findings reflect substantially the first year of the pandemic, when some strategies to increase the service capacity were implemented. Therefore, long-term consequences of these changes have not been evaluated [ 37 ]. Some studies may have been performed later and/or submitted to a journal for peer review.…”
Section: Discussionmentioning
confidence: 99%
“…doctors or nurses). Considering that today "all health professionals [are recommended to] be educated to deliver patient-centered care as members of an interdisciplinary team, emphasizing evidence-based practice, quality improvement approaches, and informatics" (Greiner and Knebel, 2003, p. 3), we recommend that all fluid workforce in healthcare must also be selected with the same care and precision as all other types of employees to protect the patients or peers from any potential harm (Edge Admin, 2020 The COVID-19 pandemic has shown that countries use different mechanisms to address the immediate needs of the health sector, for example by recruiting health workers through temporary contracts, or the use of volunteers and health workers with foreign qualifications (Tursunbayeva and Di Lauro, 2022). Many of these short-term workforce adjustments in response to the COVID-19 pandemic were examples of the fluid workforce in the health sector.…”
Section: Recruitment and Selectionmentioning
confidence: 99%
“…The COVID-19 pandemic has shown that countries use different mechanisms to address the immediate needs of the health sector, for example by recruiting health workers through temporary contracts, or the use of volunteers and health workers with foreign qualifications (Tursunbayeva and Di Lauro, 2022). Many of these short-term workforce adjustments in response to the COVID-19 pandemic were examples of the fluid workforce in the health sector.…”
Section: Health Sector and Fluid Workforce Managementmentioning
confidence: 99%
“…During the first waves, prolonged ICU stay and extensive duration of ventilator therapy contributed to the scarcity of ICU capacity 7 8. An additional severe point of concern was the restriction of human resources, which limited the available ICU capacities and demanded new strategies for recruiting more staff 9…”
Section: Introductionmentioning
confidence: 99%
“… 7 8 An additional severe point of concern was the restriction of human resources, which limited the available ICU capacities and demanded new strategies for recruiting more staff. 9 …”
Section: Introductionmentioning
confidence: 99%